Escolas cívico-militares no Paraná sob a égide neoconservadora. - Giacomin, Marcia Gevieski (2024)
The general objective of this research is to analyze the scenario of militarization of public schools in the state of Paraná under the neoconservative aegis. As for specific objectives, we propose: a) revisit the conservative neoliberal situation that supports the militarization of education in Brazil in recent years; b) identify policies and legislation regarding the militarization of schools in the country, especially after the 2018 election; c) analyze the content implicit in two documents in the process of militarization of schools in the state of Paraná between the years 2020 and 2024, identifying their impacts on school management and student training. The organization of the research is designed into three chapters according to research line 2: Society, knowledge and education at the State University of Western Paraná – UNIOESTE. The first chapter entitled neoliberal conjuncture of a conservative nature in Brazil addresses issues of conservative neoliberal policies and their consequences for education; the public school privatization process; Operation Lava Jato in Paraná as a means of strengthening the extreme right; the contributions of the Policy Cycle to understanding the context of influence in the militarization process in Paraná; reforms for education: changes in government, new Secondary Education and Common National Curriculum Base and the correlations with the conservative discourse of the militarization of schools; concepts about militarization and militarized schools and, ending the chapter, we bring the materialization of conservative policy through the creation of the Subsecretariat for the Promotion of Civic-Military Schools (SECIM) and the National Program for Civic Military Schools – PECIM. In the second chapter, we have the militarization of schools: in the state of Paraná, history and data analysis. In this history, we show how the conservative idea grew and strengthened in the state to the point where we currently have 312 militarized schools. The data is revealing and demonstrates the radical advancement of this process after 2020. Finally, the third chapter brings militarization and human formation and what the school management documents reveal in this teaching format. We asked about the democratic management of the school and why it does not match the militarization profile; the formative principles of the framework for the elaboration of the Basic Education School Regulations of Paraná and, the last item, analyzes the Manual of Civic-Military Colleges and its contradictions for human training, remembering that this training constitutes a historical struggle with teachers committed to quality public schools. The importance of the research seeks to clarify the apparent contradictions in the discourse of the ruling class and what the content analysis points out, according to Bardin (2011) in the documents that guide civic military schools. Thus, it is concluded that, although militarization can meet certain desires for order and discipline, it presents considerable challenges for the political and social formation of students. It is expected that the study will contribute to the perception of how the principles of militarization in schools come closer to or move away from the political, social and humanizing training that is so necessary today, according to the theoretical basis that founded this work.